Paleoenvironmental evolution of Picos de Europa (Spain) during marine isotopic stages 5c to 3 combining glacial reconstruction, cave sedimentology and paleontological findings. (15th November 2020) - Ballesteros, Daniel; Álvarez-Vena, Adrián; Monod-Del Dago, Mael; Rodríguez-Rodríguez, Laura; Sanjurjo-Sánchez, Jorge; Álvarez-Lao, Diego; Pérez-Mejías, Carlos; Valenzuela, Pablo; DeFelipe, Irene; Laplana, César; Cheng, Hai; Jiménez-Sánchez, Montserrat
Abstract: In glaciated areas, the environmental evolution before MIS 2 is usually poorly constrained mainly due to the later glacial erosion during the global Last Glacial Maximum (LGM). However, in carbonate areas, karst caves can preserve records of pre-LGM paleoenvironment. We studied a cave (1350 m altitude) to establish the paleoenvironmental evolution of a glaciated karst area in Picos de Europa (SW Europe). For this objective, a glacial reconstruction, cave sedimentology analyses, and macro- and micromammal remains are com bined with ten U–Th, OSL and AMS 14 C ages. The paleo-glacial reconstruction indicates glaciers descended down to 810–1040 m of altitude covering an area of 36.18 km 2 in the surroundings of Covadonga Lakes during the glacial local maximum, with the equilibrium line altitude located at 1524 ± 36 m. The geomorphological study of the cave and the U–Th and OSL dates reveal the presence of three allochthonous alluvial sediment sequences at 132–135, 98–60 and ca. 36 ka. These last two sequences would come from the erosion of fluvioglacial sediments including teeth fragments of Pliomys coronensis (= P. lenki ), an unusual species in high areas of NW Spain during the Upper Pleistocene. In addition, remains of chamois ( Rupicapra pyrenaica ) dated in 37–33 cal ka BP constitutes the oldest evidence of chamois above 800 m asl in the region. All the presented data indicate the development of alpine glacier-free areas covered by fluvioglacial sediments at ca. 1450 m altitude at 98–60 and 37–33 ka, corresponding to glacial retreat stages. Highlights: Paleoenvironmental evolution based on glacial, cave, fossils, U–Th, OSL and 14C data. Cave and mammal fossils data constrain the timing of reconstructed glaciers. Pliomys coronensis lived up to 1400 m in NW Spain during MIS 4. The oldest evidence of Rupicapra pyrenaica above 1000 m asl of NW Spain. Fossil remains indicate ice-free conditions around 98–60 and 37–33 ka at 1400 asl